1993
DOI: 10.1177/036354659302100118
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of radiographs in the evaluation of unilateral and bilateral anterior cruciate ligament injuries

Abstract: A review of 250 cases of surgical reconstruction of the anterior cruciate ligament identified 24 patients with bilateral complete tears of the anterior cruciate ligament. Twenty of these patients had previous reconstruction of one anterior cruciate ligament before rupture of the opposite ligament. Twelve injuries occurred during the same activity that was responsible for the initial opposite injury. The average time between surgical reconstruction and rupture of the opposite ligament was 29.3 months (range, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 10 publications
3
68
1
7
Order By: Relevance
“…18 Notch width index has been traditionally used as an indicator of stenosis (NWI < 0.20) of intercondylar notch. 8,16,17 Notch width index in this study was found to be 0.29, which is very similar to what was obtained by Ameet KJ et al, 12 Ravichandran et al, 6 Wada et al 5 Since there is a strong correlation between stenosis of femoral intercondylar notch and tears of ACL, 15,16 it can be inferred from our study that chances of ACL injury is less in North Indians, NWI being 0.29.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…18 Notch width index has been traditionally used as an indicator of stenosis (NWI < 0.20) of intercondylar notch. 8,16,17 Notch width index in this study was found to be 0.29, which is very similar to what was obtained by Ameet KJ et al, 12 Ravichandran et al, 6 Wada et al 5 Since there is a strong correlation between stenosis of femoral intercondylar notch and tears of ACL, 15,16 it can be inferred from our study that chances of ACL injury is less in North Indians, NWI being 0.29.…”
Section: Discussionsupporting
confidence: 89%
“…6 The shapes of the intercondylar notches were observed by many investigators. 8,16,17 Shepstone et al concluded that the shape of the notch may be of some significance (in relation to ACL damage). The notch shape may be of importance, because femora could be of equal notch width (or notch width index), but have different shapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of the patients at the time that radiographs were taken was 17 years (range [14][15][16][17][18][19][20][21]. The self-reported mean height and weight of the patients was 174.2±10.4 cm and 72.7±18.2 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Since that time, several authors have evaluated the role of a narrow intercondylar notch as a risk factor for acute ACL injury. While the majority of studies do suggest that notch stenosis is associated with a higher risk of ACL injury [2][3][4][5][6][7], others did not find significant differences between notch measurements of uninjured athletes and subjects with ACL tears [8][9][10]. We know of only one report focussing on the notch width in a paediatric population [11].…”
Section: Introductionmentioning
confidence: 99%